REVIEW OF ENVIRONMENTAL FEATURES OF THE JAVA SEA - Bambang Sadhotomo (Research Center for Fisheries, 2006)
Old information and recent data were synthesized in order to reveal comprenhensrve description of the environment feature of the Java sea. Descriptive analysis was performed on various format of data